Developing Technopreneur Skills to Face Future Challenges - Choi, Lee Kyung; Iftitah, Naura; Angela, Putri (Pandawan Sejahtera Indonesia, 2024)
In the era of globalization and rapid technological advancement, developing technopreneur skills is crucial for facing future challenges. This study aims to explore and develop effective technopreneurial skills in anticipating market changes and technological innovations. The method used in this research is SmartPLS, which enables path modeling for the analysis of latent variables related to technopreneurial skills. The findings indicate a significant relationship between entrepreneurial education, work experience, and technological readiness with the effectiveness of technopreneurial skills. The implications of this research are that educational institutions and industry stakeholders need to provide more programs and training focused on technopreneurial skills, not only from a theoretical aspect but also in practice. The contribution of this research is providing a framework that can be used by educational institutions and industry players to design and evaluate more effective entrepreneurship programs in facing future economic and technological challenges.